Analisis dan Perancangan Sistem Informasi Penjualan dengan Metode FAST pada CV Ide Karya Semesta - Muhammad Febrilian Dwi Syahputra; Buce Trias Hanggara; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CV Ide Karya Semesta is a startup engaged in consulting services and 3D engineering design training. CV Ide Karya Semesta requires a sales information system, because the current system is still manual and unable to support the company's operations. The purpose of this research is to document system design starting from modeling business processes, compiling requirements specifications, designing systems in the form of UML diagrams, prototypes, and mockups, as well as evaluating system design. System analysis and design was carried out using the four initial stages of the FAST (Framework for the Application of System Thinking) method. In the first three stages, the FAST method resulted in the identification of system problems which were analyzed with the PIECES framework, as-is business process modeling, identification of actors, requirements specification, functional and non-functional requirements. At the logical design stage, it produces system design in the form of UML diagrams in the form of use case diagrams, use case scenarios, activity diagrams, sequence diagrams, class diagrams, CDM, PDM, wireframes, and mockups. The results of the evaluation of the system design using the traceability matrix method show that the system design, starting from business process modeling, requirements specifications, to mockup design has been fulfilled in its entirety. Then the evaluation of the design using the consistency analysis method showed the results of the system design had a 100% consistency percentage value and the system was included in the correctness category in the correctness test.